Optimalisasi Pengelolaan Sumber Daya Rumput Laut sebagai Penggerak Ekonomi Baru dalam Mendukung Pembangunan Berkelanjutan - Nurul Hidayat; Haikal Nur Musyafak; Regita Aqsa Rizki Cahyani; Risna Indah Muliana; Maya Anggren; Marleni Marleni; Qalsum Nur J (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2025)
Pantai Amal Baru Village, East Tarakan District, Tarakan City, is a coastal area in Tarakan City that has abundant tourism potential and marine resources. The majority of the people of Tarakan City rely on resources in coastal areas as their livelihoods, especially as seaweed cultivators, fishermen, and coastal natural tourism drivers. Tarakan City has a fairly high potential for cultivating fishery commodities, one of which is seaweed resources, which are products of economic value as industrial raw materials that are urgently needed in the global market. However, seaweed cultivators face several problems, including capital, production costs, unstable market demand, unstable seaweed prices, and seaweed workers who do not have enough knowledge and skills regarding the improvement of seaweed processing in Tarakan City. This service activity was held in Pantai Amal Baru Village, East Tarakan District, Tarakan City, North Kalimantan Province on September 16, 2024 at 09.00-16.00 WITA. This activity was carried out at the seaweed cultivation site of Pantai Amal Baru with the participation of IRT, seaweed workers, and also small children. The methods carried out in this service activity are community education, improving the quality of seaweed cultivation, and documentation. This service activity describes the comprehensive objectives of the community service program which includes aspects of marine resource management and economy in the coastal community of Amal Baru Beach. This includes community education, improving the quality of seaweed cultivation, developing seaweed processing and increasing income.